A needs analysis on the demands of Malaysian industries for spoken English communication skill at the workplace: a concept paper / Zachariah Aidan Druckman ... [et al.] - Druckman, Zachariah Aidan; Shafie, Nurul Hidayu; Abdullah, Normah; Christ Dass, Laura (Universiti Teknologi MARA, 2022)
English Spoken Communication (ESC) is a skill that is very much needed at the workplace in Malaysia. It’s a skill that is currently required of our graduates in most local businesses. This concept paper seeks to propose a qualitative phenomenological research study which employs semi-structured interviews in conducting a needs analysis involving local industries, and undergraduates, specifically interns, with regards to their demands on the ESC skills needed from our local undergraduates upon graduation. At the present, most academic papers published on needs analyses in Malaysia are inclined to a quantitative approach or of a mixed-method approach which are heavier on the quantitative aspect which is aimed at a specific industry only. There is a scarcity of research employing a full qualitative approach on the needs analysis which focuses on multiple industries. This concept paper aims to bridge that gap and help to identify the relevant ESC skills needed in a Malaysian workplace, the usability of said skills, and the expectations of future graduates with regards to ESC. The proposed method of analysis will be thematic analysis, codifying and organizing the data in order for a conclusion to be drawn. It is hoped that with this concept paper, a clearer picture on the English language needs relative to the Malaysian tertiary education can be addressed.